Serum IMA and LP-PLA2 Levels in Patients with Coronary Heart Disease and Their Correlation with the Degree of Myocardial Ischaemia and Their Diagnostic Value - Likui Zhang; Zipeng Li; Ning Li (Emergency Medicine International)
Purpose. To measure serum levels of ischaemia-modified albumin (IMA) and lipoprotein-associated phospholipase A2 (LP-PLA2) in patients with coronary heart disease (CHD) and to analyse their correlation with the degree of myocardial ischaemia and their diagnostic value. Methods. A sample of 150 patients diagnosed with CHD by coronary angiography in our hospital from March 2019 to September 2021 was taken as the CHD group. The patients were divided into acute myocardial infarction (AMI) group (n = 52), unstable angina pectoris (UAP) group (n = 54), and stable angina pectoris (SAP) group (n = 44) according to the degree of myocardial ischaemia, and then 50 healthy physical examination patients were selected as the health group during the same period. Serum C-reactive protein (CRP), interleukin-6 (IL-6), IMA, and LP-PLA2 levels were measured in each group separately. Multiple ordered logistic regression was used to analyse the factors influencing the degree of myocardial ischaemia in patients with CHD. Pearson correlation was used to analyse the correlation between serum IMA, LP-PLA2 levels and serum CRP, IL-6 levels in CHD patients. The diagnostic value of IMA alone, LP-PLA2 alone, and in combination for CHD was analysed using receiver operating characteristic (ROC) curves. Results. In terms of serum CRP, IL-6, IMA, and LP-PLA2 levels, the CHD group was higher than the health group, the AMI and UAP groups were higher than the SAP and health groups, and the AMI group was higher than the UAP group (P<0.05). Multiple ordered logistic regression analysis showed that serum CRP, IL-6, IMA, and LP-PLA2 levels were all independent influences on the degree of myocardial ischaemia in patients with CHD (P<0.05). Pearson correlation analysis showed a positive correlation between serum IMA, LP-PLA2 levels and serum CRP, IL-6 levels in CHD patients (P<0.001). The area under curve (AUC) for serum IMA levels to predict myocardial ischaemia in patients with CHD was 0.754 (95% CI: 0.684–0.825), with a sensitivity of 61.3% and specificity of 84.0% when the best cut-off value was 0.453; the AUC for serum LP-PLA2 levels to predict myocardial ischaemia in patients with CHD was 0.747 (95% CI: 0.681–0.813), with a sensitivity of 62.0% and specificity of 82.0% when the optimal cut-off value was 0.440; and the AUC of IMA + LP-PLA2 for predicting myocardial ischaemia in patients with CHD was 0.892 (95% CI: 0.847–0.938), with a sensitivity of 86.7% and specificity of 80.0% when the optimal cut-off value was 0.667. The specificity was 80.0%. Conclusions. Serum IMA and LP-PLA2 levels are elevated in patients with CHD. Serum IMA and LP-PLA2 levels are closely related to the degree of myocardial ischaemia and its inflammatory level, and the combination of IMA + LP-PLA2 can improve the diagnosis efficacy of myocardial ischaemia in CHD patients.